Penguatan Ekosistem Kewirausahaan Desa Naioni Kota Kupang Berbasis Digitalisasi dan Kecerdasan Buatan Untuk Meningkatkan Daya Saing dan Keberlanjutan UMKM Lokal - Theresia Fouk Leu; Agatha Helena Deze; Agustina Sadri Yathy Lay; Tri Suris Lestari (Jurnal Pengabdian Masyarakat, 2026)
The development of MSMEs in rural areas still faces various challenges, particularly low digital literacy, limited access to technology, and the suboptimal utilization of artificial intelligence in supporting business activities. These conditions have an impact on the low competitiveness and sustainability of businesses, especially in Naioni Village, Kupang City, which has entrepreneurial potential based on local resources. This community service activity aims to strengthen the village entrepreneurship ecosystem through the integration of digitalization and artificial intelligence to enhance the capacity, competitiveness, and sustainability of local MSMEs. The method used is a participatory approach through stages of needs identification, training, mentoring, and hands-on practice in the use of digital technology and AI. The results of the activity show a significant increase in participants’ digital literacy and understanding of AI, increased adoption of technologies such as business social media, marketplaces, and data-based applications, as well as a positive impact on MSME performance, indicated by increased revenue, expanded market reach, operational efficiency, and product innovation. This activity also encourages a shift in the mindset of business actors to become more adaptive and technology-oriented. Thus, strengthening the entrepreneurship ecosystem based on digitalization and artificial intelligence has proven effective in supporting sustainable local economic transformation.